2014
DOI: 10.1021/tx500122x
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Aristolochic Acids, Their Major Metabolites, and Related Compounds

Abstract: Plants from the Aristolochia genus have been recommended for the treatment of a variety of human ailments since the time of Hippocrates. However, many species produce the highly toxic aristolochic acids (AAs), which are both nephrotoxic and carcinogenic. For the purposes of extensive biological studies, a versatile approach to the synthesis of the AAs and their major metabolites was devised based primarily on a Suzuki–Miyaura coupling reaction. The key to success lies in the preparation of a common ring-A prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…AL-I-NOSO 3 and AL-I-NOH were synthesized as described previously (42). Probenecid (water soluble) was purchased from ThermoFisher Scientific (catalog P36400).…”
Section: Aa-i Treatment In Cells Cultured In Mpsmentioning
confidence: 99%
“…AL-I-NOSO 3 and AL-I-NOH were synthesized as described previously (42). Probenecid (water soluble) was purchased from ThermoFisher Scientific (catalog P36400).…”
Section: Aa-i Treatment In Cells Cultured In Mpsmentioning
confidence: 99%
“…AL‐I‐OH and AL‐II‐NOH were synthesized in our laboratory as described (Attaluri et al ), and AA‐I was purified from A. indica by high‐performance liquid chromatography. AA‐related compounds were dissolved in dimethyl sulfoxide (DMSO) at 30–40 mM and stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the controversy regarding the enzymes involved in the bioactivation of AA remains, because it was reported that following AA‐I exposure, transgenic mice carrying the functional human SULT1A1‐SULT1A2 gene cluster accumulate comparable levels of AL‐DNA to that detected in the parental strain deficient in the murine sult1a1 and sult1a2 (Arlt et al ). Therefore, it is important to assess fully the mechanisms and enzymes involved in the activation of N ‐hydroxyaristolactams, which latter we are capable of synthesizing on demand (Attaluri et al ).…”
Section: Introductionmentioning
confidence: 99%
“…1A) were synthesized as described previously (35, 36). The oligonucleotide, 5’CCATCATCTCCAGAC A GATCCTCACAC (Fig.…”
Section: Methodsmentioning
confidence: 99%